Changes of sperm morphology in Duroc, Landrace and Large White boars depending on the ambient temperature during the year - V Kamanova; P Nevrkla; Z Hadas; J Lujka; R Filipcik (Veterinární Medicína, 2021)
Utilisation of artificial insemination has led to the increased role of male animals. They significantly contribute to the efficiency of productivity; therefore, sperm quality has been emphasised. The aim of this study was to analyse changes in the boar sperm morphology during the year in forty-two Duroc, Landrace and Large White boars in the Czech Republic. For each boar, a spermiogram was evaluated every month in 2018. The number of morphologically abnormal spermatozoa was recorded every month to evaluate the morphology. The abnormalities were categorised as abnormalities of the head, abnormalities of the acrosome, proximal cytoplasmic droplets and abnormalities of the tail. Throughout the study, the temperature in the stable was monitored. Changes in the sperm morphology were recorded in all breeds during the year, the changes were different for each breed. In the Landrace boars, the highest concentrations of morphologically abnormal spermatozoa were observed in July and August (P < 0.05). In this period, the concentration of the tail defects increased (P < 0.05), while, in October, a higher concentration (P < 0.05) of spermatozoa with defects of the acrosome was recorded in the Landrace boars. In the Duroc and Large White boars, the highest morphologically abnormal spermatozoa values were observed in September and October (P < 0.05). In the Duroc boars, the increase in the morphologically abnormal spermatozoa in this period was mainly caused by an increased occurrence of proximal cytoplasmic droplets (P < 0.05). On the contrary, in the Large White boars, the increase was related to a higher incidence of tail defects (P < 0.05). These results show that changes in the sperm morphology are influenced by the ambient temperature and the breed.